Novel solitary wave and periodic solutions for the nonlinear Kaup–Newell equation in optical fibers - Wang, Kang-Le (Optical and quantum electronics, 2024)
The primary objective of this study is to examine the behavior of the nonlinear Kaup-Newell equation. By employing the modified Kudryashov method and extended tanh function method, we have successfully derived novel solitary wave and periodic solutions. These new solutions are presented in trigonometric, hyperbolic and exponential function types. The proposed two approaches are efficient, direct and fascinating. These newly discovered solutions are illustrated using two-dimensional and three-dimensional graphs, incorporating suitable parameters values. These graphs are crucial for elucidating the dynamic properties of optical fibers.